A three-dimensional numerical meso-approach to modeling time-independent deformation and fracturing of brittle rocks. (January 2020) - Zhou, Guang-lei; Xu, Tao; Heap, Michael J.; Meredith, Philip G.; Mitchell, Thomas M.; Sesnic, Ashley Stanton-Yonge; Yuan, Yang
Abstract: A new 3D numerical mesoscale model is proposed to describe the time-independent deformation and fracturing of brittle rocks that accounts for material heterogeneity and local material degradation. The concept of renormalization at the mesoscale was introduced to capture the co-operative interaction of microcracks. The maximum tensile stress criterion and the Drucker-Prager criterion (which considers all three principal stresses) were used to evaluate the damage of specimen-forming elements in tension and shear, respectively. Simulations are presented alongside experimental data to show the capabilities of the model in tackling the failure process of intact rock, with an emphasis on microcrack initiation and propagation. We demonstrate that our model is capable of simulating the initiation and propagation of microcracks in deforming rocks and captures the mechanical behavior, strength, and failure patterns seen in laboratory experiments. Our 3D model therefore emerges as a powerful tool to study the evolution of failure in brittle rocks.